It pays to have an eye for emotions: Emotion recognition ability indirectly predicts annual income. (13th November 2014) - Momm, Tassilo; Blickle, Gerhard; Liu, Yongmei; Wihler, Andreas; Kholin, Mareike; Menges, Jochen I.
Summary This study integrates the emotion and social influence literatures to examine how emotion recognition ability (ERA) relates to annual income. In a sample of 142 employee–peer–supervisor triads from a broad range of jobs and organizations, we find that people's level of ERA indirectly relates to how much they earn per year. The relationship between ERA and annual income is mediated sequentially through political skill and interpersonal facilitation. The results imply that emotional abilities allow people not only to process affect‐laden information effectively but also to use this information to successfully navigate the social world of organizations in the pursuit of prosperity. Copyright © 2014 John Wiley & Sons, Ltd.